UNJUK KERJA MOTOR SUZUKI SMASH 110 CC DENGAN BAHAN BAKAR KOMBINASI BROWN GAS DAN BENSIN - Arther Adolof Rantung; Hardi Gunawan; I Nyoman Gede (JURNAL POROS TEKNIK MESIN UNSRAT, 2012)
One of the alternative fuel mixture that can be used by the gasoline motor is Brown's Gas. The gas is produced from the electrolysis solution of baking soda inside the elektrolizer. Percentage of baking soda solution is 99.45% destilled water and 0.55% baking soda.This research used a Suzuki Smash 110 cc motorcycle. Testing performed with engine speed of 1500, 2000, 2500 rpm. The testing time is 2, 3, 5, 8, and 10 minutes. Observation and calculation showed that the average rate of fuel consumption respectively are 125,7, 176,5, and 243,0 gr/h for gasoline and are 96.4, 121,9, 171,6 gr/h for motor combination brown gas and gasoline. From the above results it’s obtained that the efficient fuel consumption is 171,6 gr/h that is with engine speed 2500 rpm.Linear regression model is y = -5.919 x + 204.7 (R ² = 0.858), while quadratic regression model is y = -2.226 x ² + 20.72 x + 145.5 (R ² = 0.541). The quadratic regression fit better to the data for the coefficient of determination closer to 1.Keywords: Gasoline Motorcycle, Suzuki Smash 110 cc, Brown Gas